AB0316 Bone Mass, Osteoprotegerin and Vitamin D: Relation with Endothelial Dysfunction in Rheumatoid Arthritis Patients. (10th June 2014) - Delgado-Frías, E.; Ferraz-Amaro, I.; Lόpez-Mejias, R.; Genre, F.; Ubilla, B.; Hernández-Hernández, V.; Gόmez Rodríguez-Bethencourt, M.; González-Díaz, A.; de Vera-González, A.; González-Rivero, A.; Díaz-González, F.; González-Gay, M.
Abstract : Background: In the general population, low bone mineral density (BMD)has been independently associated with cardiovascular disease. This relationship in patients with rheumatoid arthritis (RA) is not entirely understood. Objectives: To study whether BMD, osteoprotegerin and vitamin D levels are associated with endothelial dysfunction in patients with RA. Methods: 197 women (100 RA patients, 97 controls) adjusted for age and comorbidity were recruited. BMD by dual energy X-ray absorptiometry (DEXA) of the hip, lumbar spine and total body;plasma levels of vitamin D and osteoprotegerin and arterial flow-mediated dilatation by brachial ultrasound were assessed, in both groups.Multivariate analysis and trend tests were performed to study the relationship between bone mass and endothelial dysfunction. Results: RA patients showed lower lumbar bone mass values (β coef. gr/cm 2 -64 [95%CI -122 to 6], p=0.03) and a decreased percentage of total body bone mass (β coef -0.3% [95%CI, 0.5 to 0.1], p=0.01) after adjustment for age and comorbidity. Although values tended to be lower in RA in other areas such as femoral neck, total hip, Ward's triangle, or femoral shaft, these differences were not statistically significant. Osteoprotegerin levels were significantly higher in RA (log osteoprotegerin β coef -0.19 vs 0.62 ng/mL, p=0.00), while vitamin D levels tended to be lower (log vitamin D, 3.56 vs β coef. 3.66 ng/mL, p=0.19) but no statistical significance was reached.Patients exhibited lower flow mediated dilatation in comparison to controls (β coef. -5.5% [95%CI, 9.9 - 1.1], p=0.01). Vitamin D levels in controls, were positively related to the flow-mediated brachial dilatation after adjustment for age, percentage of total body bone mass and vascular comorbidity (β coef. 0.74% [95%CI -0.02-1.48], p=0.05). This relationship was not found in patients with RA. In our study, osteoprotegerin levels were not associated with endothelial dysfunction in both controls and patients.In healthy subjects, for each quartile decrease in brachial dilatation (after adjustment for age and other variables) we found inferior bone mass values in the femoral neck (β coef. T-score 0.68 [95%CI -0.00-1.35], p for linear trend =0.05), total hip (β coef. T-score 0.84 [95%CI -0.21-1.46], p=0.01 linear trend), femoral trochanter (β coef. T-score 0.78 [95% CI 0.13-1.42], p=0.02 for linear trend) and Ward's triangle (β coef. T-score 0.62 [95% CI -0.05-1.28], p=0.06 for linear trend); this relationship was not found in lumbar spine and percentage of total body bone mass. When this analysis was performed in RA patients, the endothelial dysfunction values were not associated with bone mass. Conclusions: In controls, BMD and vitamin D levels are associated with endothelial dysfunction.This association was not found in RA patients, suggesting that the relation of bone mass with endothelial damage may depend on the disease itself and not in relation with these parameters. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2039